Metal–Organic Framework‐Based Hybrid Frameworks. Issue 2 (16th November 2020) - Shan, Yuying; Chen, Liyu; Pang, Huan; Xu, Qiang
Abstract : Framework materials, such as metal–organic frameworks (MOFs) and covalent organic frameworks (COFs), offer huge potential for applications in many aspects due to their well‐defined topologies, high crystallinity, inherent porosity, and chemical tunability. One advanced concept of further functionalizing the single framework materials is to construct hybrid frameworks (e.g., MOF‐on‐MOF, MOF‐on‐COF, and COF‐on‐MOF). Herein, different MOF‐based hybrid frameworks with complex compositions and well‐designed structures show excellent properties that cannot be achieved by single framework materials. The synthetic approaches of MOF‐based hybrid frameworks and their related applications are summarized. The opportunities and challenges for MOF‐based hybrid frameworks are also discussed. Abstract : Design and synthesis of metal–organic framework (MOF)‐based hybrid frameworks with different structures, such as MOF‐on‐MOF, MOF‐on‐COF, and COF‐on‐MOF, are reviewed. The MOF‐based hybrid frameworks show synergistic effects between the components, demonstrating high potential in a variety of applications, such as catalysis, gas adsorption and separation, and sensing.